Constituting human rights : global civil society and the society of democratic states - Frost, Mervyn (Routledge advances in international relations and politics, 2003)
Global civil society and the society of democratic states are the two most inclusive and powerful global practices of our time. In this book Frost claims that, without an understanding of the role that individual human rights play in these practices, no adequate understanding of any major feature of contemporary world politics from 'globalization' to 'new wars' is possible. Therefore, Constituting Human Rights argues that a concern with human rights is essential to the study of international relations. Global civil society comprises those millions of people worldwide who claim first generation rights for themselves. By doing so they constitute one another as civilians. The language of rights used in this practice indicates that it is a practice that is open to all and without borders. Strikingly, the validity of claims made in it are not conceptually linked to any specific legal system or sovereign state. Within democratic states, however, the participants constitute one another as holders of citizenship rights, as people with a right to participate in self-government.; Frost holds that the rights claims made in this practice are only real insofar as they build on the civilian rights of the earlier practice. An understanding of the centrality of rights claims and the practices in which they are located provides a much needed guide to all of us concerned to understand contemporary international relations and concerned about ethical conduct in world affairs. This exercise in constitutive theory puts forward a powerful tool with which to tackle some of the pressing ethical issues of our time such as those to do with refugees, asylum seekers, new wars, secessionist movements, international labour practices and many more.